The Effect of Personality and Quality of Work Life (QWL) on the Work Productivity of Middle School Teachers - Gina Permata; Bedjo Sujanto; Matin Matin (STAI Miftahul Ula Nganjuk, 2020)
study aims to obtain information about the influence of personality and quality of work life on the work productivity of state high school teachers in region I of the administrative city of East Jakarta. This research is an Associative quantitative research. The research was conducted using a survey method with the data analysis technique used to answer the hypothesis is the path analysis technique. The population in this study were 801 respondents, and a sample of 267 respondents who were selected using random sampling. The research is focused on two aspects that determine work productivity; Personality and Quality Of Work Life. The results of the analysis conclude that (1) there is a direct influence of Personality on Work Productivity, (2) there is a direct influence of Quality of Work Life on Work Productivity, (3) there is a direct influence of Personality on Quality of Work Life.